Determination of the Optimum Weight/Age and Composition of Broiler in Tropical Environment. - Williams, Adebayo R. (Obafemi Awolowo University, 2014)
In a study to determine optimum slaughtering age of broilers in Nigeria, 605 Cobb broilers were raised on floor pens, the birds were weighed weekly and 2 birds/pens were slaughtered fortnightly from six to sixteen weeks. Body weight, carcass weight, abdominal fat thickness and fat weight were measured. Internal body fat was determined by ether extraction of homogenized whole carcass less bone. Two way analysis of variance, simple and multiple regression and correlation analysis were carried out.